EKSPLORASI DAN IDENTIFIKASI PARASITOID HAMA Plutella xylostella PADA TANAMAN KUBIS Brassica oleracea - Yustina Maria Silvia Wonga Puu (AGRICA, 2014)
This study aims at exploring and identifying parasitoid Plutella xylostella pest on cabbage plants Brassica oleracea in Nduaria Village and finding out the most dominant parasitoid associated with Plutella xylostella pest. Observation variables used included identification of parasitoid species being parasitic in each stage of Plutella xylostella pest life found in the field, parasitoid species abundance and domination of parasitoid. The result of exploration in three sub-villages of NduariaVillage indicated that there were three species of the parasitoid, namely eggof parasitoid Trichogrammatoidae cojuangcoi, the larva of parasitoid Diadegma semiclausum and Cotesia Plutellae. The dominant parasitoid is Diadegma semiclausumwith the value of 0,11. The most abundance in parasitoid larva Diadegma semiclausum is 5,7%. Damage intensity caused by Plutella xylostella was categorized as medium damage intensity of>25-?50%, and this kept rising along with the age of larva and population as well as supporting environment condition due to Plutella xylostella resistance to the pesticide.